2017
DOI: 10.1007/s10802-016-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Deviant Peer Affiliation as an Explanatory Mechanism in the Association between Corporal Punishment and Physical Aggression: a Longitudinal Study among Chinese Adolescents

Abstract: Previous research has focused primarily on corporal punishment as a cause and adolescents' physical aggression as an outcome. However, there is a large gap in knowledge of the potentially bidirectional association and explanatory mechanism underlying the association between corporal punishment and physical aggression. The current study, using a longitudinal design across three time points (the fall semester of 7th grade, the fall of 8th grade, and the fall of 9th grade), aimed to a) examine the reciprocal proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 75 publications
1
40
0
Order By: Relevance
“…In line with their theorizing, the level of aggression in the peer group predicted individual group members' later aggression, despite the high temporal stability of the individual level of aggression across approximately 6 months. Similarly, Zhu et al () observed that affiliation with aggressive peers in 7th and 8th grades predicted aggression in 8th and 9th grades, respectively, in a sample of male and female adolescents from China, controlling for temporal stability and participants' gender, age, and socioeconomic status.…”
Section: Evidence Of the Spreading Of Aggression In Peer Groupsmentioning
confidence: 89%
“…In line with their theorizing, the level of aggression in the peer group predicted individual group members' later aggression, despite the high temporal stability of the individual level of aggression across approximately 6 months. Similarly, Zhu et al () observed that affiliation with aggressive peers in 7th and 8th grades predicted aggression in 8th and 9th grades, respectively, in a sample of male and female adolescents from China, controlling for temporal stability and participants' gender, age, and socioeconomic status.…”
Section: Evidence Of the Spreading Of Aggression In Peer Groupsmentioning
confidence: 89%
“…Moreover, 22.3% of participants came from rural areas, 27.4% came from county seats, 41.9% came from small cities, and 8.3% came from large cities. Furthermore, 73.4% of participants’ mothers’ and 70.4% of their fathers’ education level was high school or less, and 52.2% of families had a per capita average monthly income of more than ¥ 3000, which is higher than the average in China in 2015 ( Guangdong Statistical Yearbook, 2015 ; Zhu et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…During adolescence, time spent with family steadily decreases and an increasing amount of time is spent in the company of peers (Zhu et al, 2016; Lin et al, 2018; Tian et al, 2019). Prior research has repeatedly shown that affiliate with deviant peers plays an important role in shaping adolescent problem behaviors including aggressive behavior (Longobardi et al, 2017; Zhu et al, 2017; Lin et al, 2018). According to the social development model (Hawkins and Weis, 1985; Choi et al, 2005), parental psychological control may promote the risk of adolescents affiliating with deviant peers, which in turn may increase adolescent delinquencies such as aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%